2017
DOI: 10.1515/hc-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

An improved and scalable synthesis of zolpidem via a CuI/BINOL-mediated tandem reaction of imine and alkyne

Abstract: An improved and scalable method for the synthesis of zolpidem (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The condensation of an α ‐bromoketone or its equivalent with 2‐amino‐5‐methylpyridine is the key step for the preparation of the imidazo[1,2‐ a ] pyridine scaffold of Zolpidem. Zhang et al [129] . in 2017 reported an efficient catalytic system, CuI/BINOL for the synthesis of the anxiolytic drug Zolpidem 164 from N ‐(4‐methyl benzylidene)pyridin‐2‐amine 162 and N,N ‐dimethyl propiolamide 163 in good to excellent yields.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
See 1 more Smart Citation
“…The condensation of an α ‐bromoketone or its equivalent with 2‐amino‐5‐methylpyridine is the key step for the preparation of the imidazo[1,2‐ a ] pyridine scaffold of Zolpidem. Zhang et al [129] . in 2017 reported an efficient catalytic system, CuI/BINOL for the synthesis of the anxiolytic drug Zolpidem 164 from N ‐(4‐methyl benzylidene)pyridin‐2‐amine 162 and N,N ‐dimethyl propiolamide 163 in good to excellent yields.…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 99%
“…[128] The condensation of an α-bromoketone or its equivalent with 2-amino-5-methylpyridine is the key step for the preparation of the imidazo[1,2-a] pyridine scaffold of Zolpidem. Zhang et al [129] in 2017 reported an efficient catalytic system, CuI/BINOL for the synthesis of the anxiolytic drug Zolpidem Metal-organic frameworks (MOFs) were established by joining metal-containing units with organic ligands to afford crystalline materials with permanent porosity. [130] In MOFs, MIL-Scheme 36.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The UPLC/MS purity of all the test compounds and key intermediates was determined to be >95%. 1 H NMR, 13 C NMR, and 19 F NMR spectra were obtained in a Joel spectrometer (Jeol, 500 MHz), in CDCl 3, CD 3 OD or DMSO operating at 500 MHz ( 1 H NMR), 126 MHz ( 13 C NMR), and 471 MHz ( 19 F NMR). The chemical shifts are reported in ppm and were referenced to the residual solvent signals (CHLOROFORM-d 1 H: 7.26 ppm, 13 C: 77.16 ppm; CD 3 OD 1 H: 3.31 ppm, 13 C: 49.00 ppm), coupling constants are reported in hertz (Hz).…”
Section: General Methodsmentioning
confidence: 99%
“…Recent advances in heterocyclic chemistry revealed that it is possible to obtain zolpidem and possibly its fluorinated analogues by applying diverse one-pot protocols or intramolecular double aza-Michael addition of 2-aminopyridines to Morita-Baylis-Hillman (MBH) acetates [ 12 ]. However, these methods require usage of special technological devices, employ hazardous reagents and necessitate fluorinated starting materials, which are not easily available from commercial sources, and thereby require extensive preparation [ 13 ]. Alternatively, zolpidem and its analogues might be prepared by lengthy six to eight step procedures, which generate large amounts of waste, require expensive starting materials, give moderate yields and are narrowed in scope [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the methodology was applied to 5-methyl-3-formyl-7-azaindole (4c) and 3-formyl benzofuran (4d), resulting in compounds (5f and 5g) with potential bioactive properties. In particular, 2-amino-5-methyl-pyridine moiety in 5f is an important starting material for synthesizing a well-known insomnia treatment, Zolpidem 42 , which can be a promising example of drugdrug conjugation. To note, 3-formyl benzofuran, another possible masked diformylmethane analog, successfully underwent the desired transformation and introduced the 2-hydroxyphenyl group on the Nilotinib, which proves the expandability of the designed transformation from diverse masked diformylmethane analogs.…”
Section: Synthetic Applicationsmentioning
confidence: 99%